An analysis of the Otis Alpha Quick-Scoring Test of Mental Ability - Portugal, Aida Colmenar 1925-
The aim of the study is to determine the usefulness of a mental ability test (Otis Quick-Scoring Test of Mental Ability-The Alpha Test: Short Form) for a testing program for the primary grades of the U.P. Elementary School. This test can be used for screening applicants to the primary grades, for ability grouping, for guidance purposes, for general instructional facilitation and for prediction of student educational achievement.